MOTHER'S KNOWLEDGE ABOUT DIETARY HABIT DURING PREGNANCY IN PUSKESMAS SAMBAU, BATAM CITY - Miralza Diza; Dyah Marianingrum (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
Fulfillment of nutritional intake and proper diet plays an important role in the health of both mother and fetus. Pregnant women with good nutritional knowledge can choose food intake that has good nutritional value and is balanced. Maternal nutritional status in pregnancy affects the nutritional status of the fetus. This study aims to determine the knowledge of mothers about diet during pregnancy. Method : The research method used is descriptive. Conducted at the Sambau health center, the study was conducted for 6 months, the population in this study were pregnant women in the third trimester who had their pregnancies examined at the Sambau Health Center, totaling 140 pregnant women. The sample in this study is 30 people. The sampling technique was carried out by consecutive sampling with the research instrument using a questionnaire. Result : The results showed that 18 respondents (60%) had sufficient knowledge, as many as 8 respondents (26.7%) had good knowledge and 4 respondents (13.3%) had insufficient knowledge. Conclusion : more than half of the respondents have sufficient knowledge (60%). Suggestions for respondents to increase knowledge and increase motivation or guidelines for mothers about choosing a pregnant woman's diet